2007
DOI: 10.3758/bf03193594
|View full text |Cite
|
Sign up to set email alerts
|

Recalling episodic and semantic information about famous faces and voices

Abstract: In this study, we used the distinction between remember and know (R/K) recognition responses to investigate the retrieval of episodic information during familiar face and voice recognition. The results showed that familiar faces presented in standard format were recognized with R responses on approximately 50% of the trials. The corresponding figure for voices was less than 20%. Even when overall levels of recognition were matched between faces and voices by blurring the faces, significantly more R responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
69
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 20 publications
9
69
2
Order By: Relevance
“…As mentioned earlier, previous research that investigated this question provided contrasting results. In the Damjanovic and Hanley (2007) study, semantic information was more frequently reported from standard than from blurred faces and, from blurred faces than from voices whereas, in the Hanley and Turner (2000) study, semantic information was recalled more often from standard than from blurred faces, but blurred faces and voices produced similar rates of semantic information retrieval. For this reason, we decided to examine this question further by using faces and voices of personally familiar persons as stimuli rather than those of famous people.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…As mentioned earlier, previous research that investigated this question provided contrasting results. In the Damjanovic and Hanley (2007) study, semantic information was more frequently reported from standard than from blurred faces and, from blurred faces than from voices whereas, in the Hanley and Turner (2000) study, semantic information was recalled more often from standard than from blurred faces, but blurred faces and voices produced similar rates of semantic information retrieval. For this reason, we decided to examine this question further by using faces and voices of personally familiar persons as stimuli rather than those of famous people.…”
Section: Discussionmentioning
confidence: 75%
“…When these problems were avoided by employing the Schweinberger, Herholz, and Steif (1997) procedure designed to limit the extent to which the speech content of the extracts could give clues to a speaker's identity, the results unambiguously indicated that more semantic details could be recalled from blurred faces than from voices even though overall recognition performance was similar for both types of stimuli. Although, these two studies (Damjanovic & Hanley, 2007;Hanley & Damjanovic, 2008) confirm the view that access to semantic information is easier from faces, even blurred, than voices, further studies are needed.…”
mentioning
confidence: 74%
See 3 more Smart Citations